Prospective of the health sector in Colombia: a starting point to implement a national symbiotic system? (2018)
This work presents a structured analysis of the functioning of the health system in Colombia, describing its financial and administrative processes, leaving a current crisis in view, obtaining as a result the substantial damage of public patrimony, saturation to the judicial system by way of guardianships, linkage of officials in crimes against the public administration and mainly transgression to the fundamental right of the population for access to health services. These symptoms point to the entry of neoliberalism into the country; that with their economic opening and free market they deposited in the hands of individuals the administration of the destined resources for the health. This is a complex system that has been in operation for more than 20 years; which will be broken down into its most visible processes for the purpose of analyzing the following work